Makna Visual Perilaku Konsumtif Dalam Serial Pay Later: Kajian Semiotika Roland Barthes - Maryati Maryati; Aka Kurnia SF (Jurnal Ilmiah Literasi Indonesia, 2026)
Consumer behavior has increasingly become a prominent characteristic of modern society, particularly in urban communities influenced by the advancement of digital technology. The study aims to reveal how visual signs in the interpretation of denotative and connotative meanings based on Roland Barthe’s semiotic theory, and the analysis of consymerist myths and their influence on puplic perception. This research employed a qualitative approach by analyzing the visual meanings represented in the Pay Later series using Roland Barthe’s semiotic framework. The findings indicate that, at the denotative level, consumerist behavior is representated through shopping activities, the use of pay later services, and the ownership of goods perceived as having high value. At the connotative level, such behavior reflects individuals’ desire to gain social recognition, enhance self-image, and conform to a modern lifestyle. At the mythological level, the Pay Later series represents a cultural construction that perceives the ownership of goods and the ability tp follow trends as symbols of success and social status. The study concludes that the Pay Later series not only represents consumerist behavior as an individual practice but also portrays it as a social phenomenon influenced by consumer culture and the accessibility of digital credit service.